DEKONSTRUKSI KRISTOLOGI DALAM PEMIKIRAN ALBERT NOLAN Sebuah Metode Perkuliahan di Seminari Tinggi - Albertus Sujoko (P3TK, Sanata Dharma University, 2013)
I used the term deconstruction instead of reconstruction as used by Harvey Cox for commenting the same book to appreciate the impressive way of how Albert Nolan writes about Jesus. He explains Jesus very differently compared with other writings on Jesus. He focuses especially on Historical Jesus and deliberately chooses the title for his book Jesus Before Christianity, published in 1976. He has an intention to present Jesus objectively as a man who lived in the first century in Palestine and he said that his book can be read with or without faith. In spite of the impossibility of such undertaking due to the fact that everything we know about Jesus is taken from the Gospel we should appreciate Nolans efforts to try such elaboration on christology from below. Nolan also writes a second book on Jesus entitled Jesus Today, A Spirituality of Radical Freedom in 2006.I am of the opinion that Nolans books on Jesus are very helpful and inspiring for the education of our candidates for priesthood in major Seminary. They offer a different perspective of Christology that will influence the way of thinking of our future priests. They have to know Jesus objectively about what Jesus was saying and doing; They have to learn to know what Jesus wants us to do. To have such knowledge and skill, they have to learn form Jesus himself and I believe Nolan has something to be contributed for that purpose.